Peningkatan Pendapatan Pemerintah Dari Sektor Pajak Melalui Pembenahan Sistem Administrasi PPn - Andreas Bambang Daryatno (Jurnal Ekonomi, 2013)
Efforts to increase revenues through Taxable Entrepreneur data revamping, Tax Invoice numbering system that there will be no is no longer done by Taxable Entrepreneur, but returned to the Directorate General of Taxes by providing serial numbers have increased state revenues from VAT in the year 2012, from the target amounted to Rp 336.1 trillion (revised national budget 2012) was realized Rp 337.6 trillion. Taxable Entrepreneurs hope that the enactment of Serial Number nationwide can give assurance that there will be no number doubles. Double Tax Invoice result to incomplete of tax invoice (long disability) that there will be no can not be credited, in addition, when the restitution of taxes is performed by Taxable Entrepreneur of the Directorate General of through Tax Office listed the Taxable Entrepreneur able to process quickly because the control system of numbering that are centralized.